Exploring Counting Processes in Early Childhood: A Study on Counting All and Counting on Strategies - Prayitno, Anton (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study aimed to describe the counting processes of counting all and counting in early childhood specifically ages 5-6. To achieve this goal, a qualitative method was employed, and the instrument used consisted of three-word problems read by the examiner. These problems were related to counting all, counting all and counting on, and counting on strategies. The study subjects were six 5-6-year-old students from a kindergarten in Malang. The data collection process began with several students being asked to provide answers and reasons regarding the given instrument. Students who provided appropriate reasons were selected as study subjects. The various results obtained included, students using different strategies, such as counting all, counting on, and a combination of counting all and counting on to solve problems. In counting all, subjects counted the quantity of the first number and proceeded with the second. However, this strategy posed difficulties for students when answering addition problems above 10, leading to the use of toes as an additional counting tool. In counting, students remembered the quantity of the first number and continued counting while extending their fingers according to the quantity of the second number. Furthermore, subjects used both strategies in close succession by transitioning from counting all to counting on when solving addition problems of numbers above 5